Web-based student Course Registration System (KRS) using the Extreme Programming (XP) method - Ali, Iman; Faizah, Novianti Madhona; Nurcahyo, Widyat; Fabrianto, Luky (Jurnal Mandiri IT, 2025)
This research aims to design and develop a web-based Study Plan Card (KRS) system. The background of this study arises from challenges in the manual KRS process, which is time-consuming, prone to errors, and complicates information access. The development method employed is Extreme Programming (XP), which enables iterative system development and responsiveness to changing requirements. Data collection was conducted through observations, interviews, and document studies. The system was developed using PHP with the CodeIgniter 4 framework and MySQL database. The results indicate that the web-based KRS system enhances the efficiency of the KRS process, reduces data entry errors, and facilitates information access for students. Key features of the system include online KRS completion, digital signing by academic advisors, and integration with other academic information systems. System evaluation shows a significant improvement in data accuracy, accessibility, and information security. In conclusion, the implementation of this web-based KRS system successfully addresses issues in the manual KRS process, improves the quality of academic services, and provides an effective solution for KRS management